The administrative impact of Yemeni jurists in the Rasulid state (626-858 AH / 1228-1454 AD) (Journal of Imam Al-Kadhim College, 2023)
of the research is to identify the The aim administrative efforts of the Yemeni jurists, what positions the jurists held, what impact this had on the administrative apparatus, and what was the position of ?the rulers of Bani Rasool towards the jurists in general,       In fact, the jurists had a wide and significant participation in the administrative aspect, except in the judiciary, the ministry, the state, and other administrative positions that were assigned to them. They were able to achieve great successes and were the highest example in honesty, honesty, and non-compromise in the decisions they issued against violators, and among the aspects of the successes that the jurists achieved He kept them in positions for many years or held more than one position at the same time. We should not forget the religious role of jurists, which we tried to hide in this study so as not to affect the main focus of the research, which is the administrative aspect
Keywords: Keywords: (jurists administrators, messenger, judges, ministers